Construction of a discursive community during a lesson study. An example of geography in a primary French-speaking class - Breithaupt, Sandrine; Pache, Alain (Έρευνα στην Εκπαίδευση, 2017)
The aim of this article is to analyse language activity during a research lesson in geography with pupils aged 8 to 12, in the French-speaking part of Switzerland. We highlight the role of discursive modes in the construction of a discursive disciplinary community.